A new synthetic route to chloride selective [2]catenanes. - Hancock, L; Gilday, L; Kilah, N; Serpell, C; Beer, P (2011)
A novel anion templation route has been developed to synthesise two new catenanes, which are observed to selectively complex chloride in protic solvent media.